1978
DOI: 10.1515/znb-1978-1233
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazine Derivatives of β-Dicarbonyl Compounds, Part I. Studies on Some Benzoylacetaldehyde Aroylhydrazones

Abstract: Abstract A series of benzoylacetaldehyde benzoylhydrazones were prepared and characterised. Their UV, IR, and 1H NMR spectra suggest the enol-imine structure rather than the keto-imine form of analogous Schiff bases. The pKa values of these aroylhydrazones were also measured and correlated with the Hammet substitution constants. Attempted cyclizations of these open-chain aroylhydrazones afforded the corresponding 5-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Thus, the 1 H NMR spectrum of compound 5 showed the presence of four singlets at δ 1.61, 1.74, 2.44 and 2.62 ppm corresponding to the presence of four CH 3 groups. Also, the presence of signal at δ 5.35 ppm for C-H proton of the acetylacetone moiety and 11.54 (OH, D 2 O exchangeable) ppm supported that the condensation product 5 exist in the enolimine structure 5a (23) . Moreover, the electronic spectrum of compound 5 was recorded in MeOH, MeOH\H 2 SO 4 (0.1 M) and MeOH\NaOCH 3 (0.1M) ( Fig.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Thus, the 1 H NMR spectrum of compound 5 showed the presence of four singlets at δ 1.61, 1.74, 2.44 and 2.62 ppm corresponding to the presence of four CH 3 groups. Also, the presence of signal at δ 5.35 ppm for C-H proton of the acetylacetone moiety and 11.54 (OH, D 2 O exchangeable) ppm supported that the condensation product 5 exist in the enolimine structure 5a (23) . Moreover, the electronic spectrum of compound 5 was recorded in MeOH, MeOH\H 2 SO 4 (0.1 M) and MeOH\NaOCH 3 (0.1M) ( Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Condensation of compound 2 with acetylacetone afforded compound 5 which could be represented by any of the three possible tautomeric forms 5a, 5b or 5c (22,23) (Scheme 2). The structure of compound 5 was confirmed through the study of its spectral data and elemental analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rateb et al reported that the initial product of the condensation of benzoyl acetone and aroyl hydrazones is predominantly the enolimino form rather than the ketoenamine form and the former on cyclization gives a 5-hydroxypyrazoline derivative which may exhibit ring-chain tautomerism in solution [32]. Figure 1 show the synthesized acylhydrazone in cyclic and several chain tautomeric forms.…”
Section: Resultsmentioning
confidence: 98%